2018
DOI: 10.1080/07448481.2018.1515761
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotion dysregulation in the association between subjective social status and eating expectancies among college students

Abstract: Objective: Research suggests that college is a risky period for changes in eating behavior and beliefs. Although social health determinants relate to health behavior changes, research has not explored subjective social status, one's societal standing, in terms of eating expectancies among college students. The present study examined the emotion dysregulation in association between subjective social status and eating expectancies among college students. Participants: Participants were a diverse sample of 1,589 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Previous research has shown self-regulation behavior to be significantly associated with coping strategies [18], learning approaches [19,20], resilience [21] and with emotions themselves [22]; it can have a regulating or dysregulating value [23,24]. Self-regulation behavior has also demonstrated its mediating value in mindfulness treatment with university students [25].…”
Section: Emotion Regulation As Individual Variable Of Learning In University Studentsmentioning
confidence: 99%
“…Previous research has shown self-regulation behavior to be significantly associated with coping strategies [18], learning approaches [19,20], resilience [21] and with emotions themselves [22]; it can have a regulating or dysregulating value [23,24]. Self-regulation behavior has also demonstrated its mediating value in mindfulness treatment with university students [25].…”
Section: Emotion Regulation As Individual Variable Of Learning In University Studentsmentioning
confidence: 99%
“…A study that measured energy intake over a two-week period indicated that SSS in the society (SSS in the community was not measured) was associated with greater energy intake after lunch [42]. Another study among college students indicated that lower SSS in the community was indirectly associated with expectations that food would help with emotion regulation through poorer emotion regulation skills [43]. Our study adds to this body of work, pointing to the importance of one's standing in the community, particularly among Black women, to their eating patterns and body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Such deficits in energy compensation may result in excessive weight gain over time, although that study did not test such effects over time [42]. In a large survey study of college students, lower SSS was related to poorer emotion regulation skills, which in turn were related to greater expectancies that food would help manage negative affect and alleviate boredom [43]. One experimental study exploring the mechanisms of the relationship between perceived social status and caloric intake found that inducing social subordination elicited social anxiety, which in turn led to increased caloric intake among people who reported a strong need to belong [44].…”
Section: Introductionmentioning
confidence: 93%
“…Smoking impairs the development of adaptive coping mechanisms and increases maladaptive coping and emotional dysregulation (McGee et al, 2013), which is the inability to manage and regulate behavioral responses to internal and external stimuli (Tull and Aldao, 2015). Relatedly, studies have shown that lower SSS is associated with emotional dysregulation (Kauffman et al, 2020;Zvolensky et al, 2017). Zvolensky et al (2017) demonstrated that higher levels of anxiety symptoms among individuals of lower SSS could be partly explained by a greater difficulty in regulating emotions compared to those of higher SSS.…”
Section: Discussionmentioning
confidence: 99%